Agribusiness Competency Level of Micro, Small and Medium Enterprises (MSMEs) in Kubu Raya Regency - Sisca Manda Nasution; Novira Kusrini; Shenny Oktoriana (STMIK Indonesia Banda Aceh, 2026)
The potential of agribusiness MSMEs (Micro, Small, and Medium Enterprises) in Kubu Raya Regency is hindered by the low competency of business actors, which is reflected in minimal product innovation, packaging design, and the underutilization of digital technology in marketing. This condition indicates weaknesses in the aspects of knowledge, skills, and mental attitude, resulting in limited market reach and low turnover. This research aims to identify the level of agribusiness competency and analyze the factors influencing it, using a sample of 83 MSME actors through purposive sampling and ordinal logit regression analysis. The results show that the agribusiness competency of MSME actors is generally in the medium category, where the knowledge aspect is high while skills and mental attitude are medium. Education, business experience, and business capital significantly influence the level of competency. It is recommended that MSME actors be encouraged to increase innovation and have the courage to step out of their comfort zone to strengthen competitiveness.